Dramatic Improvement of Subcutaneous Calcinosis by Intermittent, High-Dose Etidronate plus Cimetidine in a Patient with Juvenile Dermatomyositis. (12th November 2015) - Wakabayashi, Takayuki; Sasaki, Noriko; Chinen, Naofumi; Suzuki, Yasuo
Abstract : A 17-year-old boy with juvenile dermatomyositis presented with typical skin symptoms, mild myositis, and bilateral lower limb calcinosis. His skin and muscle symptoms responded to treatment with prednisolone and azathioprine. However, calcinosis did not improve, and the patient had a limited range of knee joint motion and resultant disturbance of daily activities. Cimetidine was combined with intermittent administration of high-dose etidronate, leading to marked improvement of both subcutaneous and muscular calcinosis with no skeletal adverse reactions during a long treatment period exceeding 5 years. As a result, the range of knee joint motion has increased and performance of daily activities has improved.